Distance to semi‐natural habitats matters for arbuscular mycorrhizal fungi in wheat roots and wheat performance in a temperate agricultural landscape. Issue 4 (17th October 2022) - Pirhofer Walzl, Karin; Ryo, Masahiro; Raatz, Larissa; Petermann, Jana S.; Gessler, Arthur; Joshi, Jasmin; Rillig, Matthias C.
Abstract: Introduction: The proximity of semi‐natural habitats and agricultural fields in an agricultural landscape leads to unavoidable biological, chemical, and physical interactions. Fungi can negatively influence, but also support crop growth in agricultural fields. Therefore, in this field study we investigated the colonisation of arbuscular mycorrhizal (AM) fungi and non‐AM fungi in winter‐wheat roots as well as winter‐wheat performance in distance to semi‐natural habitats. Materials and Methods: We sampled in an intensively managed agricultural landscape in North‐east Germany along agricultural transition zones, that is, along 50 m‐transects from semi‐natural habitats like hedgerows and glacially created in‐field ponds—so‐called kettle holes—into agricultural fields. Results: To our knowledge, we show for the first time that AM fungal colonisation in winter‐wheat roots decreased linearly with increasing distance to semi‐natural habitats while non‐AM fungal root colonisation did not change. Winter‐wheat grain yield and biomass slightly increased with increasing distance to hedgerows but not to kettle holes. This clearly shows that there is a difference between different crop performance parameters. Random forest machine learning algorithms confirmed the particular importance of distance to semi‐natural habitats for AM fungal root colonisation and for winter‐wheat grain yield. Less intensive agricultural management close to semi‐natural habitats, for example, no herbicide and pesticide applications as a result of nature protection regulations, may partly explain this pattern. However, spatial response patterns of AM but not of non‐AM fungi in wheat roots also point to changed ecological interactions close to semi‐natural habitats. Conclusion: Semi‐natural and natural habitats in agricultural landscapes are slowly recognised not only to be important for biodiversity conservation, but also for sustainable crop production. Additionally, they may also be a tool for farmers and policy makers to improve sustainable landscape management. And agricultural transition zones are spatially and temporally complex dynamic ecosystems that should be the focus of further investigations. Abstract :